Current Understanding of Antiobesity Property of Capsaicin - Narang, Nithida; Jiraungkoorskul, Wannee; Jamrus, Parinda (Pharmacognosy Reviews)
The capsaicin is an ingredient that we normally mix in food in many cultural cuisines even in fresh and dried production. Because of its anticancer, anticholesterolemic, antidiabetic, antihypertensive, anti‑inflammatory, antimicrobial, and antioxidant properties, capsaicin is used worldwide. Moreover, capsaicin is also used for the protection of cardiovascular and hepatic diseases. The electronic databases PubMed, Scopus, Web of Science, Google Scholar, and ScienceDirect were searched since 2000 to present for antiobesity term. This review article is provided the update information about the antiobesity property and mechanism of capsaicin for further researches.
Keywords: Capsaicin; chili; obesity; overweight; pepper